2019
DOI: 10.1128/jvi.01502-18
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and Mechanistic Characterization of Subtype-Specific HIV Adaptation to Host Cellular Immunity

Abstract: The extent to which viral genetic context influences HIV adaptation to human leukocyte antigen (HLA) class I-restricted immune pressures remains incompletely understood. The Ugandan HIV epidemic, where major pandemic group M subtypes A1 and D cocirculate in a single host population, provides an opportunity to investigate this question. We characterized plasma HIV RNA gag, pol, and nef sequences, along with host HLA genotypes, in 464 antiretroviral-naive individuals chronically infected with HIV subtype A1 or D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 95 publications
(137 reference statements)
1
14
0
Order By: Relevance
“…HIV group M subtypes A, B, C and D collectively account for ~75% of the global pandemic. Nef is a crucial determinant of viral pathogenesis, and also ranks among the most variable regions in the HIV genome [ 40 , 41 ], suggesting that differences in Nef function may contribute to clinical outcome. Our analysis of 339 diverse Nef clones from these four major HIV subtypes demonstrates that subtype A and C clones displayed lower ability to internalize SERINC5 compared to those from subtypes B and D. This raises the intriguing possibility that an attenuated capacity to counteract SERINC5 may contribute to decreased pathogenesis in the context of subtype A or C infection, which has been seen in regions where these strains co-circulate with subtype D [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…HIV group M subtypes A, B, C and D collectively account for ~75% of the global pandemic. Nef is a crucial determinant of viral pathogenesis, and also ranks among the most variable regions in the HIV genome [ 40 , 41 ], suggesting that differences in Nef function may contribute to clinical outcome. Our analysis of 339 diverse Nef clones from these four major HIV subtypes demonstrates that subtype A and C clones displayed lower ability to internalize SERINC5 compared to those from subtypes B and D. This raises the intriguing possibility that an attenuated capacity to counteract SERINC5 may contribute to decreased pathogenesis in the context of subtype A or C infection, which has been seen in regions where these strains co-circulate with subtype D [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…pUL26 activity appears to be supported by two other tegument proteins pUL25 and pp65 [ 211 ]. HCMV also uses another tegument protein pUL50 to affect ISGylation by targeting UBE1L, an important ligase responsible for ISG15 linkage, for proteasomal degradation [ 212 ]. Since ISGylation also regulates the activation of IFN-related pathways, some viruses have harnessed ISGylation to favor their replication.…”
Section: Viral Evasion Strategies: Blockade Of Ifn Signalingmentioning
confidence: 99%
“…Since HLA class I allele distributions differ among racial and ethnic groups worldwide (15), the pattern and diversity of HLA-APs are somewhat distinct to each race and region (9,13). In addition, a difference in sequences among HIV-1 subtypes may affect the diversity of HLA-APs (16). Thus, information about HLA-APs among different HIV-1 subtypes will be useful for development of a universal HIV-1 vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the difference in consensus sequence affected the elicitation of HLA-C*01:02-restricted GagYI9-specific T cells but not that of HLA-B*52:01-restricted RI8-specific T cells. These findings account for the difference in the accumulation of HLA-associated Gag280 mutations between the subtype A/E and B infections.A previous study on HLA-APs in Uganda revealed that 34% of the identified HLA-associated polymorphisms were significantly and differentially selected between subtypes A1 and D(16). This study showed only that the subtype A1 consensus peptide had stronger affinity for HLA-B*15:03 than the subtype D consensus peptide, as found from the analysis of one case of these HLA-APs, Nef K105R, which is selected due to theon January 3, 2021 by guest http://jvi.asm.org/ Downloaded from 20 presence of putative HLA-B*15:03-restricted epitope NefRL9 in subtype A1 but not D. Thus, this study implied that the difference in consensus sequence affects the selection of CTL escape mutations.…”
mentioning
confidence: 97%